Discontinuous operation promotes efficient continuous anaerobic treatment of effluents with high lipid content - Cavaleiro, A. J. (2007)
A mixture of skim milk and sodium oleate was fed to an upflow sludge bed reactor operated in cycles. Each cycle had a feeding phase under continuous operation and a reaction phase in batch. Five cycles were performed with organic loading rates applied during feeding phases varying between 4.4 and 8 kg COD.mˉ³.dˉ¹ and a constant hydraulic retention time of 1.6 days. In the first two cycles, 70% of the methane-COD was produced in the reaction batch phase, whereas from the third to the fifth cycles, biogas production in the reaction phase was less than 3% of total production. Overall methane yields increased steadily, from 0.67 to 0.91 kg COD-CH4.kg COD removedˉ¹. LCFA accumulated into the sludge in the first two cycles, being palmitate and stearate the dominant intermediates quantified. In the subsequent cycles no LCFA were detected in the solid or liquid phases. The specific methanogenic activity in the presence of acetate and H2/CO2 increased significantly along the operation, particularly between time zero and the end of the third cycle. These results show that a discontinuous operation promoted the development of an active anaerobic community able to efficiently convert a continuous organic load of 8.2 kg COD.mˉ³.dˉ¹, from which 50% was oleate.